Educational attainment of the mother and its relation on the child's dental behavior - Gonzales, Glenn; Managbanag, Jocera; Poblete, Lisa (Adviser).
One of the variables which needs to be analyzed for a better understanding of child behavior would be the educational attainment of the mother. The aim of this study was to determine if there is a difference between the dental behavior of child subjects whose mothers have a college degree and dental behavior of child subjects whose mothers do not have a college degree, and consequently if the educational attainment of the mother is associated with the child's dental behavior. A cross-sectional study design involving sixty 1 lA - 7 year old pedodontic patients from the Philippine Children's Medical Center (PCMC) was used as subjects. They were grouped into two (non-college and college) based on the educational attainment of the mother, with thirty per group. The mother's educational attainment was determined through a pre-operative questionnaire. The child's dental behavior was assessed through a behavior rating form, using the Frankl behavior scale at five different intervals . The statistical test used was the Mann-Whitney Test. The results show that for the PCMC child patients, those with mothers who don't have a college degree tend to be brought to the dentist only when there are dental problems, while those with mothers who have a college degree are more inclined to regularly visit their dentist. In terms of behavior at different intervals , it was shown that the higher the educational attainment of the mother, the more positive the child's dental behavior. Thus, it can be concluded that the dental behavior of the child patients at PCMC during the time period of November to December 1997 is significantly different between mothers with a college degree and those without a college degree, and consequently, that for the PCMC pedodontic patients , the educational attainment of the mothers is associated with the child's dental behavior.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.